2007
DOI: 10.1183/09031936.00095606
|View full text |Cite
|
Sign up to set email alerts
|

NT-proBNP can be used to detect right ventricular systolic dysfunction in pulmonary hypertension

Abstract: Right ventricular systolic dysfunction (RVSD) at baseline (pre-treatment) predicts early death in patients with pulmonary hypertension (PH). However, RVSD can only be detected reliably by prohibitively invasive or expensive techniques. N-terminal B-type natriuretic peptide concentration ([NT-proBNP]) correlates with RV function in PH; however, an [NT-proBNP] threshold that indicates RVSD in individual patients has not previously been determined.Twenty-five patients with PH (pulmonary arterial hypertension (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 51 publications
8
70
1
3
Order By: Relevance
“…Brain natriuretic peptide changes are correlated with RV strain and RVEF measured by CMR, and the brain natriuretic peptide differences found in our study further support our CMR fi ndings. [17][18][19] In an earlier study, RVEF change difference between survivors and nonsurvivors in PAH was 8%, further illustrating that the difference found in our study is clinically meaningful. 20 Sex differences have been well documented in diseases of the left ventricle.…”
Section: Discussionsupporting
confidence: 53%
“…Brain natriuretic peptide changes are correlated with RV strain and RVEF measured by CMR, and the brain natriuretic peptide differences found in our study further support our CMR fi ndings. [17][18][19] In an earlier study, RVEF change difference between survivors and nonsurvivors in PAH was 8%, further illustrating that the difference found in our study is clinically meaningful. 20 Sex differences have been well documented in diseases of the left ventricle.…”
Section: Discussionsupporting
confidence: 53%
“…8,16 One study found that NT-pro-BNP negatively correlated with right-ventricular ejection fraction and that it identifies patients with pulmonary hypertension and right-ventricular systolic dysfunction. 17 Our COPD patients had a slightly and nonsignificantly higher NT-pro-BNP than our healthy subjects, both at rest and during exercise. Therefore, cardiac factors may not contribute to exercise intolerance in patients with mild to moderate COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not used this biomarker as outcome measure in PH associated with lung disease. In IPAH, NT-proBNP has been shown to correlate with RV function [39] and changes in serial NT-proBNP with treatment have been shown to predict survival [40]. In COPD, NT-proBNP has been shown to predict outcome following acute exacerbations of airways disease [41][42][43], identify those with concurrent left ventricular dysfunction [42,44] and function as a screening tool for PH in COPD [45].…”
Section: Discussionmentioning
confidence: 99%